Beyond Corporate Social Responsibility (CSR) and shareholder theory: contesting the relevant context of sustainability - Jacquinet, Marc (2024)
Corporate social responsibility (CSR) has not just become mainstream practice for multinational corporations, it has also become the dominant discourse of responsibility and social obligation on the behalf of private firms, conflating the deeper questions of moral obligation into a management tool, both for communicating and compensating the impact of business as usual. Related to CSR and the literature on sustainable development, the notion of sustainability has two opposite conceptions, one weak, maintaining the practices and objectives of corporations unaltered, with a marginal technological fix, in a context of global warming and growing ecological footprint, and the other, called strong sustainability, that considers that technological progress is not enough. In the latter the very purpose of corporations, their responsibility and their actions have to be thoroughly reconsidered. This paper starts with a characterization and criticism of the concept of corporate social responsibility and business ethics.